Research on a Damage Assessment Method for Concrete Components Based on Material Damage - Hongjun Wang; Xiaodan Ren; Zhi Li; Mingsheng Tang (Buildings)
With the popularization of the concept of seismic performance-based design, the correct and quantitative evaluation of post-earthquake damage to structural components has become a research focus. Referring to the concrete constitutive relationship mentioned in the Chinese national standard GB/T 50010-2010, this study proposes a damage assessment method for concrete components based on material damage. According to the value of the uniaxial damage evolution parameter of concrete (dc(t)), the damage grades of concrete components are defined. It is specified that, when the value of dc(t) is less than the dc(t),r value corresponding to the peak concrete strain (εc(t),r), the concrete component is in a non-damaged state (Level L1). When the value of dc(t) is greater than the dc(t)u value corresponding to the concrete strain (εc(t)u), the concrete component is in a severely damaged state (Level L6). When the value of dc(t) is between these two values, the damage grade of the concrete component (levels L2 to L5) is determined using linear interpolation. To promote its engineering application, this study also proposes a quantitative expression for the damage assessment method for concrete components based on dc(t). To verify the rationality of the damage assessment method for concrete components based on dc(t), a refined model of rectangular, T-shaped, and L-shaped concrete shear wall components was established using ABAQUS software, and a nonlinear finite element analysis was carried out. The simulation results show that (a) the damage assessment method for concrete components based on dc(t) can better characterize damage to concrete shear wall components; (b) when defining the damage grades of concrete shear wall components, using dc is more reasonable than using dt; and (c), from a macroscopic perspective, the damage assessment method for concrete components based on dc(t) is more in line with actual expectations and has a higher safety factor compared with the damage assessment method for concrete components based on the concrete compressive strain (εc) mentioned in the Chinese association standard T/CECA 20024-2022.